Evaluating the in vitro efficiency of grapevine leaves against Eimeria flavescens sporozoites infecting domestic rabbits - M. Murshed; J. Al-Tamimi; W.A.Q. Hailan; S. Al-Quraishy (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Coccidiosis is a common disease in rabbits and is caused by Eimeria spp., which poses a threat to its survival. The research aims to assess the effect of the Vitis vinifera extract on Eimeria flavescens sporozoites for inhibition viability. Twenty-four-well plates with a volume of 3 mL each, each containing one thousand sporulated oocysts/mL, were subjected to seven different treatments: control of 2.5% potassium dichromate solution; five different extract concentrations 125, 250, 500, 750, and 1000μg/mL concentrations for anti-sporozoites activities. in addition, 25mg/ml of Toltrazuril was as a reference medicine. The mixture's anti-sporozoite properties were assessed, and it was able to block the E. flavescens oocysts at 125g/mL, Vitis vinifera showed the lowest inhibition of 9% and the largest suppression of 87% of the viability of E. flavescens sporozoite at 1000g/mL. Longer incubation times and higher doses usually increase the inhibition rate for sporozoite viability. Findings showed that V. vinifera leaf extract has effective activity in vitro sporozoite viability.